Reeling them in : printed New Zealand Army recruiting material 1899-1999 : a thesis presented in partial fulfilment of the requirements for the degree of Doctorate of Philosophy in History at Massey University, Manawatū, New Zealand - Wildy, Daniel (Massey University, 2018)
The decision to join the army, or any other armed service, is a significant one. Unlike most jobs, the prospect of death in violent circumstances, particularly during periods of armed conflict, is a realistic possibility. Regardless of how unattractive this proposition might be, New Zealand maintained an army made up largely of volunteers throughout the period under review: beginning with the South African War in 1899, through to the deployment to East Timor in 1999. Whether militia forces, part-time Territorials, or full-time Regulars, the army has used printed recruiting material to attract New Zealanders, both men and women, to join the potentially fatal occupation of soldiering. To be successful as items of advertising, printed recruiting material has to resonate with its audience. By assessing the various themes used to encourage generations of men and women to enlist in the army, it is possible to identify what was relevant to various audiences at particular times, and by extension, what was valued within society during certain periods. In addition, how the army portrayed its worth to society, not just its worth to potential recruits, is an important aspect of recruiting material, and one that provides further opportunities to understand New Zealand society. This thesis will demonstrate significantly greater continuity among the themes used in recruiting material, and by extension, greater continuity in social values during the period than there was change.
Listed in 2018 Dean's List of Exceptional Theses
Thesis may contain copyrighted images. Copyright holders may use the Copyright Take Down Request link below to request their removal.
Keywords: Advertising; Recruiting and enlistment; Social aspects; Masculinity in advertising; Army; Recruiting, enlistment, etc; History; New Zealand; 20th century; Dean's List of Exceptional Theses; 430320 New Zealand history